Improved Cardiac Performance with Dexamethasone Therapy in Premature Neonates: Novel Insights Using Serial Echocardiographic Assessments - Jejelola Ladele; Ayman Saker; Talal Altamimi; Andrea De La Hoz; Renjini Lalitha; Michael R. Miller; Soume Bhattacharya (Applied Sciences, 2023)
(1) Background: dexamethasone is used for the prevention and treatment of chronic lung disease (CLD) in premature neonates, and its impact on cardiac performance and pulmonary vascular resistance has not been well studied. (2) Methods: eligible neonates of <30 weeks gestational age (GA) had echocardiograms performed on them at three time points—before the initiation of dexamethasone (Echo-1), 24–48 h post the completion of dexamethasone therapy (Echo-2), and 7–14 days after course completion (Echo-3). (3) Results: 28 neonates with a 25.2 week mean GA and 652.9 g birthweight were included. The mean cumulative dose of dexamethasone was 0.98 mg/kg, given over 8–10 days. Echo-1 and Echo-2 showed a significant improvement in the right ventricular fractional area change (RV FAC 44.88 vs. 49.71, p = 0.025), tricuspid annular plane systolic excursion (TAPSE 0.65 cm vs. 0.70 cm, p = 0.013), and RV S’ (7.18 vs. 8.56, p = 0.05). The left ventricular (LV) ejection fraction was similar but with a significant increase in the LV S’ (4.77 vs. 6.01, p = 0.006). A longitudinal analysis at three time points showed a significant increase in RV FAC (0.02 units 95% CI (0.00–0.04), p = 0.037), TAPSE (0.09 units 95% CI (0.06–0.13), p < 0.001), RV S’ (0.97 units (95% CI = 0.11–1.84), p = 0.028), a reduction in the eccentricity index (0.07 units 95% CI (−0.14–−0.01), p = 0.030), and an increase in the LV S’ (0.56 units (95% CI = 0.18–0.94)). (4) Conclusion: The use of postnatal dexamethasone for the prevention/treatment of CLD in premature neonates resulted in an expected improvement in respiratory status along with a significant improvement in the echocardiographic measures of biventricular heart performance.